2018
DOI: 10.4007/annals.2018.188.1.6
|View full text |Cite
|
Sign up to set email alerts
|

On the local Birkhoff conjecture for convex billiards

Abstract: The classical Birkhoff conjecture claims that the boundary of a strictly convex integrable billiard table is necessarily an ellipse (or a circle as a special case). In this article we prove a complete local version of this conjecture: a small integrable perturbation of an ellipse must be an ellipse. This extends and completes the result in [3], where nearly circular domains were considered. One of the crucial ideas in the proof is to extend actionangle coordinates for elliptic billiards into complex domains (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 53 publications
1
92
0
1
Order By: Relevance
“…We see that there exist many notions of integrability, yet Birkhoff's conjecture remains open for all of them. However, as mentioned in Section 2, a local version was proven in [KS18].…”
Section: -Mather's Minimal Average Action (Or -Function) and Billiardsmentioning
confidence: 98%
See 2 more Smart Citations
“…We see that there exist many notions of integrability, yet Birkhoff's conjecture remains open for all of them. However, as mentioned in Section 2, a local version was proven in [KS18].…”
Section: -Mather's Minimal Average Action (Or -Function) and Billiardsmentioning
confidence: 98%
“…A short proof of this can be found using elementary planar geometry in the appendix of [GM79a]. For elliptical caustics, we follow the notation in [KS18] and [DDCRR17] by setting λ 2 = Z ≥ 0. In the context of [KS18], integrable is taken to mean that the union of all convex caustics has a non-empty interior in R 2 .…”
Section: -Mather's Minimal Average Action (Or -Function) and Billiardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though much attention it has attracted, this conjecture remains open, and only a few partial progresses were obtained. As far as our understanding of integrable billiards is concerned, the most important related results are 1) a theorem ( [2]) by Bialy which asserts that if the phase space of a billiard map is almost everywhere foliated by non-null homotopic invariant curves, then the corresponding billiard table is a disk; 2) a result ( [9]) by Innami, in which he showed that if a strictly convex billiard table admits a sequence of smooth convex caustics with rotation numbers converge to 1/2, then its boundary has to be an ellipse; 3) a result ( [5]) by Delshams and Ramírez-Ros in which they study entire perturbations of elliptic billiards and prove that any nontrivial symmetric perturbations of the elliptic billiard is not integrable (see also [4,13]); 4) and the more recent works ( [1,8,10]) by Kaloshin et al, justifying a perturbative version of the Birkhoff conjecture for billiard tables with boundary close to ellipses, assuming integrability near the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…The domain enclosed by an ellipse is 2-rationally integrable. Due to [10], any smooth one parameter family of deformations of this domain, preserving the 2-integrability, are consisted of a family of domains with ellipses as their boundary, belonging to a 5-dimensional space. Theorem 1.3 can be viewed as a finite-dimensional reduction for integrable deformations.…”
Section: Introductionmentioning
confidence: 99%